Variations in the traditional processing methods of Pentadesma butyracea butter in northern Benin - BADOUSSI, ERIC; AZOKPOTA, PAULIN; MADODÉ, YANN E.; KAYODÉ, POLYCARPE A.P.; DOSSOU, ALPHONSE; SOUMANOU, MOHAMED; HOUNHOUIGAN, DJIDJOHO JOSEPH (My University, 2014)
Pentadesma butyracea is used in the North of Benin to produce a type of butter similar to shea butter. The present work was carried out to investigate the traditional processing of butter from P. butyracea through a survey among 192 traditional butter processors from 14 sociocultural groups in five different parklands in northern Benin. Three different pre-treatments of P. butyracea kernels have been identified as the basis of the butter extraction process. The pre-treatment more frequently used (69.7 per cent of processors) consists of depulping the fruit to get fresh kernels which are first boiled for 1–2 h before sun drying for 14–30 days to get cooked and dried kernels which are involved in the next steps of the extraction process. The extraction itself involves two main steps, heating and kneading, which also vary according to processors. Ten methods of processing of P. butyracea including six new methods have been reported. Two of the newly identified methods are mostly used by Boo, Anii, and Mokolé sociocultural groups from northern Benin. The identified methods of butter processing need to be optimized and the quality of the derivate butter should be assessed, using a well-known variety of P. butyracea as the raw material.
Keywords: Pentadesma butyracea; kernels; northern Benin; traditional butter processing; sociocultural groups